Developing evidence on the primary case presentation and assessment of acute abdominal pain (colic) in the horse - Curtis, Laila (2016)
Abdominal pain (colic) in the horse is one of the most common emergency problems in the horse, but there are major gaps in the current evidence. Five original studies were undertaken to build evidence on the primary assessment of abdominal pain in the horse. The first study was a systematic review of risk factors for abdominal pain. This identified 83 publications on risk factors for colic; 47 met inclusion criteria and were reviewed and categorised. Twenty four studies were evaluated using the JBI-Mastari critical appraisal tool. Evidence from the ten publications with least susceptibility to bias was collated. There was consensus of evidence for increasing age, recent change in diet and previous history of abdominal pain are risk factors for colic. This evidence should inform veterinary practitioner’s clinical decision making and approach to disease prevention. The second study was a systematic review of diagnostic tests for abdominal pain. This identified 190 publications; 46 publications met inclusion criteria and were reviewed and categorised. Thirty studies were evaluated using the QUADAS critical appraisal tool. None of the studies used a suitable methodology to assess the value of a diagnostic test to differentiate critical cases. The outcomes of this systematic review were a description of the current evidence and recommendations for future research using appropriate study designs. Both systematic reviews highlighted a lack of evidence from primary practice. The third study was a prospective survey of the primary assessment of horses with abdominal pain by veterinary practitioners. Data was collected from 1016 cases, including clinical history, presenting signs, diagnostic and treatment approaches and case outcome. Cases were categorised as critical or non-critical. Multivariate logistic regression was used to identify clinical features associated with critical cases. Five variables remained in the final model: pain, heart rate, capillary refill time, pulse character and gastrointestinal borborygmi. These should be considered essential components of the initial assessment and triage of horses presenting with colic. The fourth study was an online survey of veterinary practitioner’s opinions of diagnostic tests for colic. Responses from 228 participants were analysed. The most frequently used tests were ‘response to analgesia’, ‘rectal examination’ and ‘nasogastric intubation’, but there was a wide variation in practitioners’ approaches. The main reasons for not using tests were that practitioners considered they were not required, or had concerns around personal safety, lack of facilities or financial constraints. The final phase was two multi-disciplinary workshops to review current evidence and generate recommendations. Fifty participants attended the first workshop and generated 84 statements on the recognition of colic. Forty one participants attended the second workshop and generated 160 statements on the assessment of horses with colic. These statements form the first phase of a multi-disciplinary Delphi process to develop best practice guidelines on the recognition and primary assessment of horses with abdominal pain. This research makes significant contributions to the current evidence on abdominal pain in the horse. It has consolidated existing information, made recommendations for future research, and worked with practitioners to address evidence gaps, and involved different stakeholders in deciding how this evidence should be applied.